2019
DOI: 10.1038/s41564-019-0607-2
|View full text |Cite
|
Sign up to set email alerts
|

Barrier bednets target malaria vectors and expand the range of usable insecticides

Abstract: Transmission of Plasmodium falciparum malaria parasites occurs when nocturnal Anopheles mosquito vectors feed on human blood. In Africa, where malaria burden is greatest, bednets treated with pyrethroid insecticide were highly effective in preventing mosquito bites and reducing transmission, and essential to achieving unprecedented reductions in malaria until 2015 1. Since then, progress has stalled 2 and with insecticidal bednets losing efficacy against pyrethroid-resistant Anopheles vectors 3,4 , methods tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 32 publications
(16 reference statements)
0
39
0
Order By: Relevance
“…The RRS imaging approach is being used in both field and lab environments to further understand the interaction between bednets and mosquitoes, including the testing of novel designs [4]. In addition, the system is helping the definition of new protocols for commercial bednet assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RRS imaging approach is being used in both field and lab environments to further understand the interaction between bednets and mosquitoes, including the testing of novel designs [4]. In addition, the system is helping the definition of new protocols for commercial bednet assessment.…”
Section: Discussionmentioning
confidence: 99%
“…This effect enables triangulation and hence recovery of 3D mosquito position data [26] but requires complex calibration and extensive signal processing. In contrast, it has been demonstrated that 2D tracking provides entomologically useful information [1,2,4] and the requirement in malaria control is to rapidly test design iterations of interventions over long time periods (hours) and with sufficient repeats to give statistically reliable data. Hence, this paper targets robust 2D tracking..…”
Section: Optical Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…37 At the opposite end of the scale there is a substantial body of experimentally 38 generated data on the behavior of individual mosquitoes in experimentally controlled 39 settings such as wind tunnels and olfactometers [13]. A wide range of possible sensory 40 modalities could influence host-seeking selection behavior in these conditions and these 41 different potential stimuli have been investigated with regard to isolated CO 2 42 concentration, olfactory [14], [15], [16], visual [17], [18], auditory [19], [20] and tactile 43 sensory cues [21], or combinations thereof [22]. 44 There is a knowledge gap between individual mosquito behavior and downstream 45 effects in terms of epidemiological disease transmission that could be filled by fine 46 grained models of insect flight behavior and host interactions.…”
mentioning
confidence: 99%
“…For example, modifications might include vectors with different arrival 359 patterns at the bed net, different host preferences, or the influence of a second human 360 host in the room, or of a residual insecticidal treatment on the wall. Recently, we used 361 an expanded version of the model to compare seven barrier bed net designs, which 362 allowed us to rapidly identify the most promising candidate(s) to fast track for further 363 evaluation [40].…”
mentioning
confidence: 99%